MORAL VALUE OF SERIES “LAYANGAN PUTUS” WRITTEN BY EKA NUR PRASETYAWATI - ace, Wildatussholiha Ridwana; Reindy Aziqar Pasya; Marudut Bernadtua Simanjuntak (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2022)
Layangan Putus is a series which air on paid application which is WeTv. This series was told us about the household of Aris and Kinan. Kinan and Aris is a wife and husband couple where their household should ruined because Aris was cheating with another woman named Lidya Danira. Kinan decided to solve their household issues through divorce. This research is analysing a lesson and value that people could take on Layangan Putus series, since this series is going viral in society, so that, it is necessary to identify and know the value and lesson in that series. The method of this research was using descriptive qualitative approach. The author of this paper was using secunder data which taken on the internet. The data collection technique was watching the full episodes of Layangan Putus series. The author of this paper then observing the series through listening to all the conversation dan dialogue from the characters in that series as well as the gestures which shown by the characters. Value and lesson which appeared in Layangan Putus must be have beneficial for the society since it can be a lesson for them to live a harmony household and make it better.